Lecture 1-Justification of the Value of Clinical Pharmacy Services and Clinical Indicators Measurements-Introductory Remarks from a Traveler on a 40-Year Wayfaring Journey with Clinical Pharmacy and Pharmaceutical Care - Richard H. Parrish; Lita Chew (MDPI AG, 2018)
Without question, health care delivery, and clinical pharmacy’s purpose in it, is changing rapidly all over the world. Pharmacy’s place in the new health care environment is ensured only to the extent that the purpose of pharmaceutical care is understood and transmitted to the global structures of these developing organizational patterns and paradigm shifts. While the current trend toward commodification of illness and treatment seems to be driving efforts to consolidate the economic factors of pharmaceutical distribution, a new type of practice—patient-driven health care—has continued to shape the interactions of pharmacists and patients all over the world. A thorough understanding of the above factors involved in pharmacy’s history, present, and future are necessary for clinical practice preparation, as well as for value justification. How clinical pharmacy will succeed in this kind of social and economic milieu is precisely why this series of lectures and roundtables will help us embrace many of the vexing issues that clinical pharmacy administrators and practitioners face in daily practice.